Estudo comparativo da precisão de modelos obtidos com guia multifuncional e index em prótese sobre implantes - Sydney, Roberto Bittencourt (2007)
Passive fit between the infra-structure and the abutments is one of the main aspects that determine the clinical success of implant-supported prosthesis. Among the clinical and laboratorial steps that may influence passivity are the transfer and impression techniques, once they affect the construction of accurate master casts. The objective of this paper is to verify the quality of master casts built from the multifunctional guide technique for impression and transfer of implants, comparing its accuracy with the precision of models built only by indexing for infra-structure fit test. Two CNC (computer numeric controlled) milled infra-structures were fabricated over 2 resin maxillas (controls): one with 6 implants in favorable positions for rehabilitation and one with 6 implants in unfavorable positions. Quality of infrastructure fit on the multifunctional guide models (test) and index was evaluated under light microscopy. The technique tested resulted in accurate models , with maximum average distortion of 5 µm from control. There were no differences between the test group and the index group, under favorable and unfavorable conditions. We can conclude that when using the multifunctional guide technique for implant impression and transfer, there is no need for indexing implants for infra-structure accuracy test, even when the fixtures are in an unfavorable position for rehabilitation.